Student Perception Of Game-Based Learning To Facilitate English Business Writing In A Flipped Classroom - Anandha Anandha; Dini Anggraheni; Adiprana Yogatama (Departement of Mathematics Education, 2023)
As the popularity of flipped learning environments continues to rise, with online content delivery and in-class activities, there is a growing necessity to assess students' readiness to participate in online work and be prepared for class. Consequently, understanding students' perspectives on Game-Based Learning (GBL) in an English Business Writing class becomes crucial. This research employed a survey to examine 59 students attitudes towards Game-Based Learning (GBL) in a flipped classroom on 4th semester Economics Faculty university students in English Business Writing class. The result of the study shows that students give positive feedback and have positive attitudes towards the use of GBL in the English Business Writing class. These findings can support educators in anticipating student apprehensions and successfully integrating a flipped learning approach in undergraduate courses, particularly in English Business Writing classes.